Cloud point extraction method for the removal of phenolic compounds from water samples using dc193c non−ionic surfactant / Nur Nadhirah Mohamad Zain - Mohamad Zain, Nur Nadhirah (2015)
A greener method based on cloud point extraction was optimized in three systems namely as cloud point extraction (CPE); CPE with β−cyclodextrin (CPE−βCD) and CPE with β−cyclodextrin functionalized with ionic liquids (CPE−βCD−IL) for removing phenolic compounds including 2,4−dichlorophenol (2,4−DCP), 2,4,6−trichlorophenol (2,4,6−TCP) and 4−nitrophenol (4−NP) in aqueous samples by using UV−Vis spectrophotometric technique. The DC193C surfactant was chosen as an extraction solvent due to its low water content in a surfactant rich phase. The parameters affecting the extraction efficiency such as pH, equilibration temperature and incubation time, concentration of surfactant, modifier, salt and analyte, volume of surfactant and modifier and water content were evaluated and optimized. In the three CPE systems, the solubilization were in proportion of the hydrophobicity of the target compounds, according to the following order; 4−NP < 2,4−DCP < 2,4,6−TCP. Langmuir model was found to fit well with the solubilization of the phenolic compounds into DC193C surfactant. The thermodynamic results indicated that the solubilization of the phenolic compounds solubilized into DC193C surfactant were feasible, spontaneous and endothermic. Finally, the inclusion complex formation, hydrogen bonding and interaction between the DC193C surfactant, β−CD, βCD−IL and the phenolic compounds were proven using the 1H NMR and 2D NOESY spectroscopy.